2012
DOI: 10.1103/physreve.85.031203
|View full text |Cite
|
Sign up to set email alerts
|

Two liquid states of matter: A dynamic line on a phase diagram

Abstract: It is generally agreed that the supercritical region of a liquid consists of one single state (supercritical fluid). On the other hand, we show here that liquids in this region exist in two qualitatively different states: "rigid" and "nonrigid" liquids. Rigid to nonrigid transition corresponds to the condition τ≈τ(0), where τ is the liquid relaxation time and τ(0) is the minimal period of transverse quasiharmonic waves. This condition defines a new dynamic crossover line on the phase diagram and corresponds to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
314
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 245 publications
(333 citation statements)
references
References 41 publications
15
314
2
2
Order By: Relevance
“…(b): longitudinal (filled black bullets) and transverse (filled red bullets) excitations in liquid Na. Open diamonds correspond to longitudinal (black) and transverse (red) excitations in polycrystalline Na, and dashed-dotted lines to longitudinal (black) and transverse (red) branches along [111] direction in Na single crystal [70]. (c): longitudinal (black bullets) and transverse (red bullets) excitation in liquid Ga.…”
Section: Experimental Evidence For High-frequency Collective Modes Inmentioning
confidence: 99%
See 1 more Smart Citation
“…(b): longitudinal (filled black bullets) and transverse (filled red bullets) excitations in liquid Na. Open diamonds correspond to longitudinal (black) and transverse (red) excitations in polycrystalline Na, and dashed-dotted lines to longitudinal (black) and transverse (red) branches along [111] direction in Na single crystal [70]. (c): longitudinal (black bullets) and transverse (red bullets) excitation in liquid Ga.…”
Section: Experimental Evidence For High-frequency Collective Modes Inmentioning
confidence: 99%
“…We have recently proposed that this picture should be modified, and that a new line, the Frenkel line (FL), exists above the critical point and separates two states with distinct properties (see Figure 10) [111][112][113][114]. The main idea of the FL lies in considering how particle dynamics changes in response to pressure and temperature.…”
Section: Frenkel Linementioning
confidence: 99%
“…The Frenkel line has recently been proposed, which separates two dynamically distinct states: the gas-like regime where particle only have diffusive motion and the liquidlike regime where particle combine both solid-like quasiharmonic vibrational motion and gas-like diffusive motion [13][14][15]. This transition take place when liquid relaxation time τ approaches Debye vibration period, τ D .…”
mentioning
confidence: 99%
“…In the simplest case the interaction energy is approximated by pair interactions only. Among the most studied in the literature is Lennard-Jones (LJ) system which has the potential U (r) = ε This system demonstrates a generic view of phase diagram of a substance containing gas, liquid and crystal phases and well describes the behavior of noble gases and some molecular substances.In our recent works it was shown that supercritical region of the phase diagram can be divided into two parts: rigid liquid and dense gas [1][2][3]. These regions differ by the microscopic dynamics of particles and are separated by a crossover line called Frenkel line.…”
mentioning
confidence: 99%
“…Several criteria can be used to locate the line of dynamical crossover [1][2][3]. Among the most convenient ones are the velocity autocorrelation function (vacf) criterion and the isochoric heat capacity one [3].…”
mentioning
confidence: 99%